Ultra high-risk PFA ependymoma is characterized by loss of chromosome 6q - Baroni, Lorena V.; Sundaresan, Lakshmikirupa; Heled, Ayala; Coltin, Hallie; Pajtler, Kristian Wilfried; Lin, Tong; Merchant, Thomas E.; McLendon, Roger; Faria, Claudia; Buntine, Molly; White, Christine L.; Pfister, Stefan; et al. (Neuro-Oncology, 2021)
AbstractBackground. Within PF-EPN-A, 1q gain is a marker of poor prognosis, however, it is unclear if within PF-EPN-A additional cytogenetic events exist which
Gesehen am 02.11.2021